2015
DOI: 10.1016/j.jclepro.2015.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the Bidirectional Biodiesel Supply Chain

Abstract: a b s t r a c tFor remote areas, small-scale local biodiesel production is particularly attractive if producers and consumers are the same. Such supply chains are labeled as bidirectional. However, little is known on how raw material supply, transportation, logistics, production and operations uncertainties impact the operational performance of such Bidirectional Biodiesel Supply Chains. This paper contributes by exploring these uncertainties in a multiple case study, directed at mobile processing of rubber se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Any policy which aims to reduce pollution will have repercussions for economic growth. Thus, analysis of the use of RE and other sustainable activities does not provide a true picture; it is the links among them that matter for the achievement of “affordable and clean energy,” “decent work and economic growth,” and “climate action” (Lu et al ., 2014; Bot et al ., 2015; UNDP, 2017). Sustainable development tends to be discussed within the frameworks of the SDGs.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Any policy which aims to reduce pollution will have repercussions for economic growth. Thus, analysis of the use of RE and other sustainable activities does not provide a true picture; it is the links among them that matter for the achievement of “affordable and clean energy,” “decent work and economic growth,” and “climate action” (Lu et al ., 2014; Bot et al ., 2015; UNDP, 2017). Sustainable development tends to be discussed within the frameworks of the SDGs.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…<Insert (Lu et al, 2014;Bot et al, 2015). The nature of the designed policies should also comply with the setting of the context.…”
Section: Comparison Of Non-parametric and Geweke Causality Analysismentioning
confidence: 99%
“…Now, if a particular renewable energy policy is aimed at reducing CO2 emissions and fossil fuel consumption, then it should also be remembered that this policy will also have short term and long term impacts on economic growth pattern. Therefore, relying on the results of one causality test might not bring out the true picture, and any unidirectional causal association should be treated with utmost care, as bidirectional nature of renewable energy policies ensure the nature of sustainable development in any economy (Lu et al, 2014;Bot et al, 2015). This study has shown the way to design renewable energy policies by assessing (i) the unidirectional causal association obtained from linear and non-linear causality tests, (ii) complementing the results of both the tests, and (iii) triangulating the results by Geweke (1982) causality analysis.…”
Section: Comparison Of Non-parametric and Geweke Causality Analysismentioning
confidence: 99%
“…This might reflect an adaptation strategy against a changing climate in which the reduction of seasonal rainfall can no longer sustain the current livelihood. For those villages with polyculture plantation livelihoods, such changes to rainfall in a remote area can be particularly challenging, since reduced production can no longer compensate for the already high cost of transporting commodities to the nearest market or city (Bot et al 2015). For those villages with freshwater fishing livelihoods, the unpredictability of seasonal rainfall can disrupt fish spawning and recruitment, as well as fishers' ability to catch fish (Welcomme & Halls 2001;Patrick 2016).…”
Section: What Drives the Change In Village Primary Livelihood Towardsmentioning
confidence: 99%